Dose escalation PET imaging for safety and effective therapy dose optimization of a bispecific antibody. Issue 1 (1st January 2020) - Wang, Yan; Pan, Donghui; Huang, Chenrong; Chen, Bingliang; Li, Mingzhu; Zhou, Shuaixiang; Wang, Lizhen; Wu, Min; Wang, Xinyu; Bian, Yicong; Yan, Junjie; Liu, Junjian; et al.
ABSTRACT: Selecting the dose for efficacy and first-in-human studies of bispecific antibodies (BsAbs) is a challenging process. Herein, positron emission tomography (PET) imaging with 89 Zr-labeled IBI322, an anti-CD47/PD-L1 BsAb, was used to optimize the safety and effective therapy dose. By labeling with 89 Zr, we aimed to assess the pharmacokinetics (PK), safety, and target engagement of IBI322 with dose escalation dynamic PET imaging in humanized transgenic animal models bearing MC38 tumors (knock-in of hCD47 and hPDL1). 89 Zr-labeled IBI322 specifically accumulated in tumors with a tumor-to-muscle ratio of 12.37 ± 1.42 at 168 h (0.22 mg/kg) and the biodistribution of normal tissues from PET imaging could be used for preliminary safety prediction. According to the Pearson correlation analysis between the ELISA-quantified serum concentration and heart uptake (%ID/g) (r = 0.980), a modified Patlak model was proposed. The exploratory target-mediated 50% (0.38 mg/kg) and 90% (0.63 mg/kg) inhibitory mass doses were calculated with the current modified Patlak model. The preliminary pharmacodynamics (PD) study with 0.34 mg/kg revealed that the dose prediction was rational. In conclusion, dose escalation PET imaging with 89 Zr-labeled antibodies is promising for PK/PD modeling and safety prediction, and helpful for determining rational dosing for preclinical and clinical trials of BsAbs.